2013
DOI: 10.7227/bjrl.89.s.11
|View full text |Cite
|
Sign up to set email alerts
|

‘Less Mudslinging and More Facts’: A New Look at an Old Debate about Public Health in Late Medieval English Towns

Abstract: Many current assumptions about health provision in medieval English cities derive not from the surviving archival or archaeological evidence but from the pronouncements of Victorian sanitary reformers whose belief in scientific progress made them dismissive of earlier attempts to ameliorate the quality of urban life. Our own tendency to judge historical responses to disease by the exacting standards of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has often been remarked that outbreaks of plague (past and present) disproportionally affect the poor more than the affluent (e.g., Wrightson 2011;Carmichael 1986), and it has been suggested that poverty-induced grain hoarding in crowded homes of poor construction create an environment where plague can flourish: this was the case in Surat (1994) as well as in Peru (1992-94) and in more recent outbreaks in Madagascar (Andrianaivoarimanana et al 2013;WHO 2008). Testing such a hypothesis for historic epidemics requires good urban environmental histories of multiple locations and time periods, as proposed by Guy Geltner (2012) and Carole Rawcliffe (2013). We cannot rely on the traditional assumption that medieval cities were seething sites of filth and vermin; the historical reality is not only much more positive than these modern prejudices would credit, it is also more complex (Rawcliffe 2013).…”
Section: Uniting the Study Of Past And Present For The Futurementioning
confidence: 99%
See 1 more Smart Citation
“…It has often been remarked that outbreaks of plague (past and present) disproportionally affect the poor more than the affluent (e.g., Wrightson 2011;Carmichael 1986), and it has been suggested that poverty-induced grain hoarding in crowded homes of poor construction create an environment where plague can flourish: this was the case in Surat (1994) as well as in Peru (1992-94) and in more recent outbreaks in Madagascar (Andrianaivoarimanana et al 2013;WHO 2008). Testing such a hypothesis for historic epidemics requires good urban environmental histories of multiple locations and time periods, as proposed by Guy Geltner (2012) and Carole Rawcliffe (2013). We cannot rely on the traditional assumption that medieval cities were seething sites of filth and vermin; the historical reality is not only much more positive than these modern prejudices would credit, it is also more complex (Rawcliffe 2013).…”
Section: Uniting the Study Of Past And Present For The Futurementioning
confidence: 99%
“…Testing such a hypothesis for historic epidemics requires good urban environmental histories of multiple locations and time periods, as proposed by Guy Geltner (2012) and Carole Rawcliffe (2013). We cannot rely on the traditional assumption that medieval cities were seething sites of filth and vermin; the historical reality is not only much more positive than these modern prejudices would credit, it is also more complex (Rawcliffe 2013).…”
Section: Uniting the Study Of Past And Present For The Futurementioning
confidence: 99%
“…It has often been remarked that outbreaks of plague (past and present) disproportionally affect the poor more than the afflu ent (e.g., Wrightson 2011;, and it has been suggested that povertyinduced grain hoarding in crowded homes of poor construc tion create an environment where plague can flourish: this was the case in Surat (1994) as well as in Peru (1992-94) and in more recent outbreaks in Madagascar WHO 2008). Testing such a hypothesis for historic epidemics requires good urban environ mental histories of multiple locations and time periods, as proposed by Guy Geltner (2012) and Carole Rawcliffe (2013). We cannot rely on the traditional assumption that medieval cities were seething sites of filth and vermin; the historical reality is not only much more positive than these modern prejudices would credit, it is also more complex (Rawcliffe 2013).…”
Section: Uniting the Study Of Past And Present For The Futurementioning
confidence: 99%
“…Testing such a hypothesis for historic epidemics requires good urban environ mental histories of multiple locations and time periods, as proposed by Guy Geltner (2012) and Carole Rawcliffe (2013). We cannot rely on the traditional assumption that medieval cities were seething sites of filth and vermin; the historical reality is not only much more positive than these modern prejudices would credit, it is also more complex (Rawcliffe 2013).…”
Section: Uniting the Study Of Past And Present For The Futurementioning
confidence: 99%